Persistent pulmonary artery hypertension in patients undergoing balloon mitral valvotomy - Nair, Krishna Kumar Mohanan (Medknow Publications & Media Pvt Ltd, 2013)
Pulmonary artery pressure (PAP) is known to regress after successful balloon mitral valvotomy (BMV). Data of persistent pulmonary artery hypertension (PPAH) following BMV is scarce. We analyzed the clinical, echocardiographic, and hemodynamic data of 701 consecutive patients who have undergone successful BMV in our institute from 1997 to 2003. Data of 287 patients who had PPAH (defined by pulmonary artery systolic pressure [PASP] of ≥ 40 mmHg at one year following BMV) were compared to the data of 414 patients who did not have PPAH. Patients who had PPAH were older (39.9 ± 9.9 years vs. 29.4 ± 10.1; P < 0.001). They had higher prevalence of atrial fibrillation (AF; 21.9 vs. 12.1%, P < 0.05), moderate or severe pulmonary artery hypertension (PAH) defined as PASP more than 50 mmHg (43.5 vs. 33.8%, P = 0.00), anatomically advanced mitral valve disease as assessed by Wilkin's echocardiographic score > 8 (33.7 vs. 23.2%, P < 0.001), and coexistent aortic valve disease (45.6 vs. 37.9%, P < 0.001) at the baseline. Those patients with PPAH had comparatively lower immediate postprocedural mitral valve area (MVA). On follow-up of more than five years, the occurrence of restenosis (39.3 vs. 10.1%, P = 0.000), new onset heart failure (14% vs. 4%, P < 0.05) and need for reinterventions (9.5% vs. 2.8%, P < 0.05) were higher in the PPAH group. Patients with PPAH were older, sicker, and had advanced rheumatic mitral valve disease. They had higher incidence of restenosis, new onset heart failure, and need for reinterventions on long term follow-up. PPAH represents an advanced stage of rheumatic valve disease and indicates chronicity of the disease, which may be the reason for the poorer prognosis of these patients. Patients with PPAH requires intense and more frequent follow-up.